Decolourization of textile effluent by adsorption on naoh treated Textile Venus Clam (Paphia Textile): article - Omar, M. R. S.; Hassan, S. S. A. S. (2018)
In this work the feasibility of employing Textile Venus Clam (TVC) to remove Basic Red 46 (BR46), an azo dye from its aqueous solutions was investigated. The parameters that influence the adsorption process such as adsorbent dosage, initial dye concentration and contact time were studied in batch experiments. The adsorption of Basic Red 46 was took place at neutral pH of 7 and room temperature. Furthermore, the adsorbent was characterized by using Brunaeur-Emmett Teller (BET) to study the surface area of the adsorbent. The TVC was washed using deionized water and treated with NaOH solution. Then the adsorbent was dried for 24 hours at 100˚C. The adsorbent then crushed and calcined at 400, 500 and 600˚C for 3 hours and stored. For the effect of adsorbent dosage, a range of dosage from 0.3-0.9g of adsorbent in 100mL of 20 ppm of BR46 solution. The process was carried out for 60 minutes in an orbital shaker at 200 rpm. For the effect of initial dye concentration, the optimal dosage was used and a range of initial concentration from 20-60 ppm of BR46 solution. The solution was shake for the same time and speed. The samples were filtered by using filter paper and the dye concentration was measured using UV-Vis Spectrophotometer. The BET analysis showed that the adsorbent has BET surface area of 2.4758 m2/g and pore volume of 0.003754 cm3/g. The highest adsorption of BR46 was at 0.9g adsorbent dosage which is 87.48% removal. The highest removal for initial concentration of 20 ppm concentration of dye was 87.6% removal. Thus, it was concluded that TVC can be used effectively as an adsorbent fort the removal of BR46 from aqueous solution.